Identification of novel SHANK2 variants in two Chinese families via exome and RNA sequencing - Wu, Yong; Li, Wenzhou; Tan, Bo; Luo, Sanchuan (Frontiers in Neuroscience, 2023)
Background: SHANK2 encodes a postsynaptic scaffolding protein involved in synapse formation, stabilization and homeostasis. Variations or microdeletions in the SHANK2 gene have been linked to a variety of neurodevelopmental disorders, including autism spectrum disorders (ASD) and mild to moderate intellectual disability (ID) in human.However, the number of reported cases with SHANK2 defects remains limited, with only 14 unrelated patients documented worldwide.In this study, we investigated four patients from three families with ID.Whole-exome sequencing (WES) was performed to explore the genetic causes, while Sanger sequencing was used to confirm the identified variants. Furthermore, RNA sequencing and functional enrichment analysis were performed on patients with likely pathogenic variants to gain further insights into the molecular landscape associated with these variants.Results: Two novel variants in the SHANK2 gene: a heterozygous splicing substitution (NM_012309.5:c.2198-1G>A p.Pro734Glyfs*22) in Family 1, and a heterozygous nonsense variant (NM_012309.5:c.2310dupT p.(Lys771*)) in Family 2 were identified by WES and confirmed by Sanger sequencing. RNA sequencing and cohort analysis identified a total of 1196 genes exhibiting aberrant expression in three patients.Functional enrichment analysis revealed the involvement of these genes in protein binding and synaptic functions.We identified two novel loss of function variants that broadens the spectrum of SHANK2 variants. Furthermore, this study enhances our understanding of the molecular mechanisms underlying SHANK2-related disorders.